Effectiveness of combined laser-puncture and conventional wound care to accelerate diabetic foot ulcer healing (Medical Journal of Indonesia, 2017)
Background: Impaired wound healing is a common complication of diabetes. It has complex pathophysiologic mechanisms and often necessitates amputation. Our study aimed to evaluate the effectiveness of combined laser-puncture and conventional wound care in the treatment of diabetic foot ulcers. Methods: This was a double-blind controlled randomized clinical trial on 36 patients, conducted at the Metabolic Endocrine Outpatient Clinic, Cipto Mangunkusumo Hospital, Jakarta, between May and August 2015. Stimulation by laser-puncture (the treatment group) or sham stimulation (the control group) were performed on top of the standard wound care. Laser-puncture or sham were done on several acupuncture points i.e. LI4 Hegu, ST36 Zusanli, SP6 Sanyinjiao and KI3 Taixi bilaterally, combined with irradiation on the ulcers itself twice a week for four weeks. The mean reduction in ulcer sizes (week 2–1, week 3–1, week 4–1) were measured every week and compared between the two groups and analyzed by Mann-Whitney test. Results: The initial median ulcer size were 4.75 (0.10–9.94) cm2 and 2.33 (0.90–9.88) cm2 in laser-puncture and sham groups, respectively (p=0.027). The median reduction of ulcer size at week 2–1 was -1.079 (-3.25 to -0.09) vs -0.36 (-0.81 to -1.47) cm2, (p=0.000); at week 3–1 was -1.70 (-3.15 to -0.01) vs -0.36 (-0.80 to -0.28) cm2, (p=0.000); and at week 4–1 was -1.22 (-2.72 to 0.00) vs -0.38 (-0.74 to -0.57) cm2, (p=0.012). Conclusion: Combined laser-puncture and conventional wound care treatment are effective in accelerating the healing of diabetic foot ulcer.